Phytochemicals and antimicrobial analysis of selected medicinal plants from Brunei Darussalam - HUSSEIN TAHA; ZULHAMIZAN AWANG-JAMIL; MUHAMMAD FAIRUZ AMINUDDIN; AIDA MARYAM BASRI; BARIRAH QURATULAIN ZAIDI; NORHAYATI AHMAD (Society for Indonesian Biodiversity, 2021)
Abstract. Awang-Jamil Z, Aminuddin MF, Zaidi BQ, Basri AM, Ahmad N, Taha H. 2021. Phytochemicals and antimicrobial analysis of selected medicinal plants from Brunei Darussalam. Biodiversitas 22: 601-606. Medicinal plants have been widely used but their pharmacological properties are yet to be fully explored. This study was aimed to determine the phytochemicals and their antimicrobial activity of four selected medicinal plants: Melastoma malabathricum, Merremia borneensis, Pandanus amaryllifolius, and Senna alata from Brunei Darussalam. Phytochemical constituents were evaluated by using gas chromatography-mass spectrometry (GC-MS) and antimicrobial screening was carried out using agar well diffusion method. A number of phytochemicals were identified in the plant extracts, of which the following compounds were present in higher amounts (>10 %): coumaran, hentriacontane, hexatriacontane, 3-hydroxy benzyl alcohol, ?-linolenic acid, palmitic acid, catechol, squalene, and ?-tocopherol-?-D-mannoside. A concentration-dependent antimicrobial activity was observed in some extracts against Bacillus subtilis, Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, and Saccharomyces cerevisiae. Results of this study showed medicinal potential of the four selected plants.